A simple and sensitive fluorescence assay for biothiol and acetylcholinesterase activity detection based on a HSA–AuNCs@Cu2+ complex. Issue 39 (25th September 2019) - Ge, Jia; Qi, Zhangyu; Zhang, Liangliang
Abstract : A simple and sensitive fluorescent turn-on method for the detection of biothiols and acetylcholinesterase activity was developed based on a HSA–AuNC@Cu 2+ complex. Abstract : Human serum albumin–templated gold nanoclusters (HSA–AuNCs) were successfully synthesized using human serum albumin (HSA) as bioscaffolds. The fluorescence of the HSA–AuNCs was quenched in the presence of copper ions (Cu 2+ ) due to the formation of the HSA–AuNC@Cu 2+ complex. With the addition of biothiols, Cu 2+ could be removed from the surface of the HSA–AuNCs via the coordination of the biological thiols with the Cu 2+ ions. As a result, an immediate fluorescence recovery occurred when the biothiols were introduced. We developed a simple and sensitive fluorescence biosensor for the detection of biothiols and acetylcholinesterase (AChE) activity based on the HSA–AuNC@Cu 2+ complex. The proposed biosensor was sensitive for the detection of cysteine and glutathione. The linear ranges for cysteine, homocysteine, and glutathione were 0–400 nM, 0–400 nM, and 0–500 nM with detection limits of 16 nM, 40 nM, and 12 nM, respectively. In addition, the proposed method could also be used for the detection of AChE activity in the range of 0–10 mU mL −1 with a detection limit of 0.05 mU mL −1 . This rapid and simple assay was successfully used for cysteine, glutathione, and AChE activity detection in human serum with a satisfactory recovery, indicating its potential in biomedical applications.